Expresión (¬p⇔q)⇒p∧¬r
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
q⇔¬p=(p∧¬q)∨(q∧¬p)(q⇔¬p)⇒(p∧¬r)=(p∧q)∨(¬p∧¬q)∨(¬q∧¬r)
(p∧q)∨(¬p∧¬q)∨(¬q∧¬r)
(p∧q)∨((¬p)∧(¬q))∨((¬q)∧(¬r))
Tabla de verdad
+---+---+---+--------+
| p | q | r | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 0 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
Ya está reducido a FND
(p∧q)∨(¬p∧¬q)∨(¬q∧¬r)
(p∧q)∨((¬p)∧(¬q))∨((¬q)∧(¬r))
(p∨¬q)∧(q∨¬q)∧(p∨¬p∨¬q)∧(p∨¬p∨¬r)∧(p∨¬q∨¬r)∧(q∨¬p∨¬q)∧(q∨¬p∨¬r)∧(q∨¬q∨¬r)
(p∨(¬q))∧(q∨(¬q))∧(p∨(¬p)∨(¬q))∧(p∨(¬p)∨(¬r))∧(p∨(¬q)∨(¬r))∧(q∨(¬p)∨(¬q))∧(q∨(¬p)∨(¬r))∧(q∨(¬q)∨(¬r))
(p∧q)∨(¬p∧¬q)∨(¬q∧¬r)
(p∧q)∨((¬p)∧(¬q))∨((¬q)∧(¬r))
(p∨¬q)∧(q∨¬p∨¬r)